2014
DOI: 10.1002/hep.26704
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular filtration rate equations for liver-kidney transplantation in patients with cirrhosis: Validation of current recommendations

Abstract: Simultaneous liver and kidney transplantation (SLKT) remains the procedure of choice for patients with both endstage liver disease and kidney failure. Stringent guidelines are needed to avoid unnecessary kidney transplantation. A recent consensus meeting proposed criteria based on the Modified Diet in Renal Disease (MDRD)‐6 equation to estimate glomerular filtration rate (GFR). The aims of this study were to compare GFR equations to true GFR in candidates for liver transplantation (LT) and to determine the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
122
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(125 citation statements)
references
References 25 publications
1
122
0
2
Order By: Relevance
“…There is an extensive literature that evaluates the performance of formulas. Several authors have questioned the reliability of these equations in diverse populations, such as type 2 diabetes mellitus, 3,4 CKD, 5,6 heart failure, 7,8 cancer patients, 9,10 liver transplantation, 11 cirrhosis, 12,13 or kidney transplantation. [14][15][16] In renal transplantation, Gaspari et al 17 evaluated 14 creatinine-based formulas and showed their poor performance in reflecting true GFR.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is an extensive literature that evaluates the performance of formulas. Several authors have questioned the reliability of these equations in diverse populations, such as type 2 diabetes mellitus, 3,4 CKD, 5,6 heart failure, 7,8 cancer patients, 9,10 liver transplantation, 11 cirrhosis, 12,13 or kidney transplantation. [14][15][16] In renal transplantation, Gaspari et al 17 evaluated 14 creatinine-based formulas and showed their poor performance in reflecting true GFR.…”
mentioning
confidence: 99%
“…[19][20][21][22] Most of the studies used only an arbitrary percentage of error that includes the majority of the estimations. In general, it is considered acceptable to observe the estimations within bounds of error of ± 30% compared with the gold standard, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] which is a wide limit of error.…”
mentioning
confidence: 99%
“…22,24 Among creatinine-based equations, it has been shown that MDRD-6 is the most accurate in cirrhosis. 25 However, in contrast to MDRD-4, MDRD-6 may underestimate true GFR, discordances being more pronounced in old patients and patients with low serum sodium. Other indirect markers of renal function such as cystatin C are available; however, they are costly and not widely available, and recent studies have shown that similar to sCr, cystatin C level is affected by muscle mass and liver disease and overestimates renal function in patients with cirrhosis.…”
Section: Pathophysiology Of Acute Kidney Injury In Cirrhosis: Inflammmentioning
confidence: 99%
“…25,68 Although duration of RRT (4-8 weeks) and GFR have been traditionally used by some centers to determine the need for simultaneous liver kidney (SLK) transplants, evidence-based guidelines for SLK are lacking. 40 Further investigations, particularly focusing on novel renal plasma protein biomarkers may provide further information on prognostication of potential post-LT renal recovery (along with cause of AKI) before making a decision to proceed with SLK transplant.…”
Section: Natural History Of Acute Kidney Injury: Pretransplant and Pomentioning
confidence: 99%
“…According to KDOQI [51] , CKD is defined as a GFR of less than 60 mL/min for more than three months, calculated using the modified diet in renal disease (MDRD)-6 formula (Appendix 4) supporting its potential usefulness in the decision making for simultaneous liver and kidney transplantation. This hypothesis has been tested in patients with stable cirrhosis in the study of Francoz et al [52] . They showed that MDRD-6 formula was superior to MDRD-4 and Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) formulas identifying stable cirrhotic patients with markedly impaired renal function, including those with ascites (Table 3).…”
Section: Major Criteriamentioning
confidence: 99%